Environmental Disclosure As An Absolute Determinant Of The Profitability Of Nickel Mining Companies - Fathya Anindita; Pradana Jati Kusuma; Ana Kadarningsih; Vicky Oktavia (Jurnal Telekomunikasi dan Informatika, 2026)
Environmental, Social, and Governance (ESG) disclosure has become an important strategy for promoting sustainable business practices and enhancing corporate performance, particularly in environmentally sensitive industries such as nickel mining. However, previous studies have reported inconsistent findings regarding the relationship between ESG disclosure and financial performance. Therefore, this study examines the effects of overall ESG disclosure and its individual dimensions Environmental (E), Social (S), and Governance (G) on the financial performance of nickel mining companies listed on the Indonesia Stock Exchange during the 2021–2025 period. This study employs a quantitative approach using secondary data obtained from quarterly, annual, and sustainability reports. Panel data regression was estimated using the Panel EGLS method with cross-section weights, followed by a nonlinear regression analysis to further examine the relationship between the Social dimension and financial performance. The results indicate that overall ESG disclosure does not significantly affect Return on Equity (ROE). However, Environmental and Governance disclosures have positive and significant effects on financial performance, whereas Social disclosure has a negative but insignificant effect in the linear model. An additional nonlinear analysis suggests a possible, though not statistically significant, U-shaped pattern (turning point of 0.905), tentatively indicating that the financial benefits of social disclosure may emerge only after companies achieve a higher level of social disclosure; this nonlinear pattern warrants further confirmation in future research. These findings highlight the importance of evaluating ESG dimensions individually, as their contributions to financial performance differ and evolve over time.